Pēterburgas Zinātņu akadēmijas rakstu krājumi Latvijas Universitātes Muzejā - Kuzņecova, Kristīne (My University, 2019)
Latvijas Universitātes Muzeja Botānikas un mikoloģijas kolekcijās glabājas Pēterburgas Zinātņu akadēmijas 18. gs. beigās – 19. gs. sākumā izdotā rakstu krājuma 27 sējumi - Acta Academiae Scientiarum Imperialis Petropolitanae (12 sējumi) un Nova Acta Academiae Scientiarum Imperialis Petropolitanae (15 sējumi). Raksts satur informāciju par Pēterburgas Zinātņu akadēmijas izveidi un rakstu krājuma publikāciju visražīgākajiem autoriem.

Botany and Mycology collections of the Museum of the University of Latvia contain the records of the St. Petersburg Academy of Sciences. 27 volumes (Acta Academiae Scientiarum Imperialis Petropolitanae (12 volumes) and Nova Acta Academiae Scientiarum Imperialis Petropolitanae (15 volumes)) of the collections of articles have been published at the end of the 18th century and beginning of the 19th century. The article contains information about the establishment of the St. Petersburg Academy of Sciences and the most prolific authors of these article collections.
Collections of articles of the St. Petersburg Academy of Sciences in the Museum of the University of Latvia
Keywords: Research Subject Categories::HUMANITIES and RELIGION::History and philosophy subjects::History subjects::History of science; Pēterburgas Zinātņu akadēmija; The Saint Petersburg Academy of Sciences; Acta Academiae Scientiarum Imperialis Petropolitanae; Nova Acta Academiae Scientiarum Imperialis Petropolitanae; zinātņu vēsture; rakstu krājums